The Relationship Between Self-Concept and Memory Motivation with Memory Procrastination on Students at Nurus Shofa Student Islamic Boarding School Malang - Ahmad Fathan Abidi; Suryanto Suryanto; Endang Retno Surjaningrum (MANAZHIM, 2022)
Students who memorize the Qur'an in carrying out their duties on campus and in Islamic boarding schools simultaneously make students inconsistent with the process of memorizing the Qur'an. It takes motivation and self-concept to minimize procrastination by knowing self-image through experiences from interactions with the environment. The purpose of this study was to determine the level of self-concept, motivation, procrastination in students who memorized the Qur'an and the relationship between self-concept and procrastination, motivation and procrastination, as well as self-concept and motivation with delays in memorizing students. The method used is quantitative with a purposive sampling technique. The research sample amounted to 58 people. The scale used is CVR (Content Validity Ratio) and then analyzed using Pearson correlation calculations. The results showed a negative and significant relationship between self-concept and memorization procrastination. This is indicated by the correlation coefficient (rxy) of -0.536 with p = 0.000 (p < 0.05). The higher the self-concept of students, the lower the procrastination of memorizing students. While the results of the study between memorization motivation and memorization procrastination showed a positive correlation. This is indicated by the correlation coefficient (rxy) of 0.461 with p = 0.000 (p < 0.05). These results indicate no significant correlation between memorization motivation and memorization procrastination.